How to digitalize inseparable service processes: the enabling role of internal and external support for innovation - Anna Moker; Prisca Brosi; Isabell M. Welpe (Business Research, 2020)
Across industries, firms face the need to digitalize their service processes, i.e., transform the service delivery from a physical into a digital form or enhance it through digital technologies. Therefore, one important challenge can arise due to the inseparability of service processes, which describes the necessity for a customer to consume a service the moment which a service provider produces it. Since existing research has failed to examine inseparability as a predictor of service digitalization, this study aims to explore whether inseparability hinders the digitalization of service processes and whether internal support in form of innovation culture and external support from third parties can help to mitigate the influence of inseparability. Data from an online survey of 204 German service employees and managers confirm our hypotheses. These results demonstrate to practitioners that although it may be more difficult to digitalize service processes due to their inseparability, firms may rely on internal and external support for innovation to overcome this challenge.
Keywords: 650; Digitalization; Service process; Inseparability; Externalsupport for innovation; Internal support for innovation